Simulation model of security control system functioning: A case study of the Wroclaw Airport terminal. (September 2017) - Kierzkowski, Artur; Kisiel, Tomasz
Abstract: A security control system is the key element at an airport because each passenger must undergo security check before boarding. Security control must be performed efficiently while maintaining a high level of safety. This article presents a security control model that is applied at a given airport. A set of variable input data describing the model and data received by the user as a result of its use is presented. The security control model is developed using the FlexSim software and based on security control model implementation, for which algorithm for managing the security checkpoint operation schedule are used. The algorithm allows a capacity lack margin to be established in the security control system in order to lower the system operation cost and maintain an acceptable passenger service quality. We describe two basic patterns of implementing the security control process: single- and double-lane counters. The security control counter has been divided into specific areas (queues). The developed model was implemented into the management system of the security checkpoint at Wroclaw Airport. Measures of the system's capacity are determined for the following sample input data (system characteristics and the stream of passenger reports): the average duration of a passenger's stay in the security control system and the number of operator work hours depending on the adopted management strategy. The developed model can be used in existing security control systems and also to evaluate the operation of a system at its design stage. Highlights: A model of security control was developed. An algorithm for dynamic management of a security checkpoint was developed. Characteristics of the system operation were obtained for dynamic and static management. Reduced process costs were obtained.